DEVELOPMENT OF TEACHING MATERIALS TO SUPPORT THE MERDEKA CURRICULUM IN REDOX REACTIONS AND ELECTROCHEMISTRY FOR PHASE F SENIOR HIGH SCHOOL - Jasmine, Nalisha; Mawardi, Mawardi; Suryani, Okta; Akmar, Reza (Chimica Didactica Acta, 2024)
AbstractThe research aims to evaluate the development of teaching materials that incorporate multiple representations of chemical concepts, specifically on the topic of redox and electrochemistry, to support the Merdeka Curriculum and enhance students mental models in Phase F of senior high school. Educational Design Research (EDR) was the chosen methodology and the study involved three university chemistry lecturers, two chemistry teachers, and nine students. Data collection was carried out using validity and practicality questionnaires. The results revealed that the average construct validity score of 0.87 and the average content validity score of 0,86 classified the materials as valid. Furthermore, the practicality assessment showed that this teaching material received a high practicality score, with a score of 97% from teachers and 92% from students indicating ease of application in learning. In conclusion, the teaching materials developed for redox and electrochemistry lessons, incorporating multiple chemical representations, were proven to be both valid and highly practical, supporting the goals of the Merdeka Curriculum in fostering deeper student understanding.